Tumors induce complex DNA damage in distant proliferative tissues in vivo - Redon, Christophe E. (National Academy of Sciences, 2010)
That tumors cause changes in surrounding tissues is well documented, but whether they also affect distant tissues is uncertain. Such knowledge may be important in understanding the relationship between cancer and overall patient health. To address this question, we examined tissues distant to sites of implanted tumors for genomic damage using cohorts of C57BL/6 and BALB/c mice with early-stage subcutaneous syngeneic grafts, specifically, B16 melanoma, MO5076 sarcoma, and COLON26 carcinoma. Here we report that levels of two serious types of DNA damage, double-strand breaks (DSBs) measured by γ-H2AX focus formation and oxidatively induced non-DSB clustered DNA lesions (OCDLs), were elevated in tissues distant from the tumor site in tumor-bearing mice compared with their age- and sex-matched controls. Most affected were crypts in the gastrointestinal tract organs and skin, both highly proliferative tissues. Further investigation revealed that, compared with controls, tumor-bearing mice contained elevated amounts of activated macrophages in the distant gastrointestinal tissues, as well as elevated serum levels of several cytokines. One of these cytokines, CCL2/MCP-1, has been linked to several inflammation-related conditions and macrophage recruitment, and strikingly, CCL2-deficient mice lacked increased levels of DSBs and OCDLs in tissues distant from implanted tumors. Thus, this study is unique in being a direct demonstration that the presence of a tumor may induce a chronic inflammatory response in vivo, leading to increased systemic levels of DNA damage. Importantly, these findings suggest that tumors may have more profound effects on their hosts than heretofore expected.